Arm Wrestling and Humeral Fractures: A Case Series - Shivashankara; Gowthaman Nambiraj; Rishab Chandraprakash; Dilip kumar E Naidu; L Sabari Vaasan (Journal of Clinical and Diagnostic Research)
Humeral shaft fractures are common injuries seen in the increasingly popular sport of arm wrestling. They occur due to a combination of axial load and twisting forces on a fixed elbow. Hereby, the authors present a case series of four cases of humeral shaft fractures, all of which presented within an hour of injury. Two of the four patients had oblique fractures, one had a spiral fracture, and one had a comminuted fracture. Additionally, one of the patients had an associated radial nerve injury immediately following the injury. All were managed with fixation by plating, and the radial nerve injury was treated with dynamic splinting. On follow-up, all four patients showed radiological and clinical signs of union, and radial nerve function returned to normal. These fractures occurred at the junction of the middle and distal thirds of the humeral shaft, a site that carries the risk of injuring the radial nerve due to its course. Therefore, the present case series aimed to determine the mechanism of injury, identify the type of fractures and associated nerve injuries seen in such cases, compared these findings with available literature, and ascertain the clinical outcomes of managing such injuries.